Changes in suspected adverse drug reaction reporting via the yellow card scheme in Wales following the introduction of a National Reporting Indicator. Issue 8 (7th April 2022) - Deslandes, Paul N.; Bracchi, Robert; Jones, Karen; Haines, Kath E.; Carey, Emma; Adams, Alana; Walker, Jenna; Thomas, Alison; Routledge, Philip A.
Abstract : Aims: This study aimed to assess the impact of a National Reporting Indicator (NRI) on rates of reporting of suspected adverse drug reactions using the Yellow Card scheme following the introduction of the NRI in Wales (UK) in April 2014. Methods: Yellow Card reporting data for general practitioners and other reporting groups in Wales and England for the financial years 2014–15 (study period 1) and 2015–16 (study period 2) were obtained from the Medicines and Healthcare Products Regulatory Agency and compared with those for 2013–14 (pre‐NRI control period). Results: The numbers of Yellow Cards submitted by general practitioners in Wales were 271, 665 and 870 in the control period, study period 1 and study period 2, respectively. This is equivalent to an increase of 145% in study period 1 and 221% in study period 2 compared with the 12‐month control period (2013–14). Corresponding increases in England were 17% and 37%, respectively ( P < .001 chi–squared test). The numbers of Yellow Cards submitted by other groups in Wales were 906, 795 and 947 in each of the study periods. Conclusions: Introduction of the NRI corresponded with a significant increase in the number of Yellow Cards submitted by general practitioners in Wales. General practitioner reporting rates continued to increase year on year through to 2018–19 with the NRI still in place. No concomitant change was found in reporting rates by other groups in the health boards in Wales.